Amiodarone-induced thyrotoxicosis: type 1 or type 2?. (27th October 2014) - Khan, Ahsan; Puttanna, Amar; Raskauskiene, Diana
Abstract : A 69-year-old man presented with a 6-week history of shortness of breath on exertion, unintentional weight loss, altered bowel habits and lethargy. He was diagnosed with atrial fibrillation 2 years previously and started on amiodarone and warfarin. He subsequently reverted to sinus rhythm and his medication was stopped 1 year prior to presentation. He denied history of thyroid dysfunction. On examination, he had a small firm goitre of grade I. His skin was warm and sweaty. Thyroid function tests showed him to be thyrotoxic. He was started on carbimazole 20 mg; however, he further became significantly thyrotoxic. Given the severity of his presentation and lack of any clinical or biochemical improvement, oral prednisolone 30 mg once daily was coadministered. His symptoms subsequently resolved and he became euthyroid. The prednisolone was tapered down and stopped while the carbimazole was incrementally reduced to 10 mg daily.